2018
DOI: 10.1109/tbcas.2018.2845856
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cholesterol Monitoring With Smartphone as Miniaturized Electrochemical Analyzer for Cardiovascular Disease Prevention

Abstract: Currently, cardiovascular diseases become one of the major threat to human's life. The early prevention of cardiovascular diseases plays a critical role in the healthcare engineering. Point of care monitoring the blood lipid level is capable of making the positive contribution to the prevention of cardiovascular disease. Ubiquitous smartphones paved the way as the flexible and widespread platform for the interaction of various health information. In this manuscript, we report the world's first medical smartpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Imaging techniques are not popular in this category, as the adapter consists of special electronics that are designed specifically to target a unique chemical compound . Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone‐based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures to ) . Zhao et al, as shown in Figure A, developed a fluorescent smartphone‐based label‐free sensor to detect Fe (III) by employing the quenching effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging techniques are not popular in this category, as the adapter consists of special electronics that are designed specifically to target a unique chemical compound . Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone‐based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures to ) . Zhao et al, as shown in Figure A, developed a fluorescent smartphone‐based label‐free sensor to detect Fe (III) by employing the quenching effect.…”
Section: Resultsmentioning
confidence: 99%
“…[168][169][170][171][172][173][174] Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone-based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures 10 to 13). [175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192] Zhao et al, 193 as shown in Figure 8A, developed a fluorescent smartphone-based label-free sensor to detect Fe (III) by employing the quenching effect. The 3D printed adapter uses a 365-nm UV LED and a smartphone camera.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%
“…[26,27]. On the other hand, smartphone-based sensory system has been widely used in biomedical application, food security, and environmental analysis at the point of care setting [28][29][30][31][32][33][34][35][36][37][38][39][40]. The integration of AI/machine learning with smartphonebased sensory system can make the detection more accurate and higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: xbcen@scu.edu.cn Abbreviations: HCT, hematocrit; ICU, intensive care unit ical dongle to detect the whole blood creatinine for the proactive renal health management [11]. It is reported that the sensory module can be integrated directly with smartphone to provide the blood test function such as uric acid, glucose, total cholesterol, and triglyceride [12][13][14]. In the family setting, we reported the usage of TV remote controller as the medical device for diabetes manage of glucose level [15].…”
Section: Introductionmentioning
confidence: 99%